IMPLIKASI PENDIDIKAN DALAM PRESPEKTIF AL QUR'AN : TELAAH TERHADAP SURAT AL ISRA' AYAT 36, AN NUR AYAT 24, DAN YASIN AYAT 65 TERHADAP MENUNTUT ILMU - Erni Setyowati; Eri Kusumawati, Yusi Susanti, Muhammad Syaifullah (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
In demanding science should not done at will so as to underestimate the process. Because, there are important stages that must be passed by muslims in the process so as not to get lost. Findings from this study as stated in essence from QS. Al-Isra verse 36 are that every muslim must do charity and speak basedon science, probihited from taqlid to someone, probihited from fanatics based on lust and must realized thathearing, vision and heart are selections tools in the process of demanding science and all these tools wil beheld accountable before Allah. The corelationin surah An-nur verse 24 and surah Yassin verse 65 explain that on the day of judgment their thongue , hands, and feet will be witnesses of what they have done during their life on eart. And it is also explained in surah Yassin verse 65 that on the day of resurrection there will be body parts that will bear witness to one’s actions while in this world. This research aims to determine whether there is an influence resulting from Al-Qur'an education Surah Al-Isro verse 36, An-nur verse 24 and Yassin verse 65 on students in studying. The method used in this research is descriptive qualitative in the form of written and verbal data. Researchers explain, describe and group data objectively with the aim of describing existing data, then research around the themes raised in a comprehensive, structured and objective manner. The results of this research illustrate that there is an influence from Al-Qur'an education Surah Al-Isro verse 36, An-nur verse 24 and Yassin verse 65 on students in studying.